2016
DOI: 10.1188/16.cjon.606-610
|View full text |Cite
|
Sign up to set email alerts
|

Advantages and Limitations of Wearable Activity Trackers: Considerations for Patients and Clinicians

Abstract: The global market for activity trackers is growing, which presents clinicians with a tremendous opportunity to incorporate these devices into clinical practice as tools to promote activity. This article highlights important considerations about tracker accuracy and usage by cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…A major limitation of recent studies on the validity testing of actigraphs was that most evaluations of the intensity of daily PAs have been conducted in laboratories, whereas actigraphs are usually applied in free-living environments [8,22]. Because of the favorable ecological validity of field experiments [45], in the present study, a randomized controlled trial was conducted that assigned participants with different experimental treatments in actual environments.…”
Section: Methodsologymentioning
confidence: 99%
See 2 more Smart Citations
“…A major limitation of recent studies on the validity testing of actigraphs was that most evaluations of the intensity of daily PAs have been conducted in laboratories, whereas actigraphs are usually applied in free-living environments [8,22]. Because of the favorable ecological validity of field experiments [45], in the present study, a randomized controlled trial was conducted that assigned participants with different experimental treatments in actual environments.…”
Section: Methodsologymentioning
confidence: 99%
“…Recent studies have indicated that although the validity for step counting of consumer-grade activity trackers is acceptable [32], they may have lower validity for energy expenditure (EE) and sleep compared with other criterion measures [22]. Low accuracy in activity tracking might mislead and jeopardize professional clinical judgments, because these trackers are widely used as a reference for improving public health [8]. Research-based actigraphs are conventionally and widely used in medical evaluations of sleep and rest, such as the studies of circadian rest-activity cycles by Brown et al [33] and wake-sleep conditions by Cole et al [34] and Matsumoto et al [35].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in commercial wearable technology has led to multiple devices that can enable PA to be assessed objectively. Of these, the accelerometer is commonly used for quantifying activity intensity and counting the number of steps [4]. Accelerometers are inexpensive, easy to use and longlasting.…”
Section: Introductionmentioning
confidence: 99%
“…Both these devices do have some form of computer with integrated sensors that can collect information relating to the user (Haghi, Thurow, & Stoll, 2017;Peltola, 2017). Due to their attentive and communicative qualities wearables devices have attracted attention from developers in various fields including health, fitness, sport, art and industrial applications (Walker, Hickey, & Freedson, 2016). Software and hardware developments in the wearables platform continue to grow due to the increased adoption of these devices for health monitoring purposes (Hutton et al, 2018).…”
Section: Introductionmentioning
confidence: 99%